2010
DOI: 10.1021/nn101554u
|View full text |Cite
|
Sign up to set email alerts
|

Radially Aligned, Electrospun Nanofibers as Dural Substitutes for Wound Closure and Tissue Regeneration Applications

Abstract: This paper reports the fabrication of scaffolds consisting of radially aligned poly(ε-caprolactone) nanofibers by utilizing a collector comprised of a central point electrode and a peripheral ring electrode. This novel class of scaffolds was able to present nanoscale topographic cues to cultured cells, directing and enhancing their migration from the periphery to the center. We also established that such scaffolds could induce faster cellular migration and population than nonwoven mats consisting of random nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
234
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 272 publications
(249 citation statements)
references
References 42 publications
5
234
0
3
Order By: Relevance
“…Another approach was developed by Chvojka et al [22] who produced PVA nano yarns using a special saw-like collector, by twisting electrospun PVA nanofibers and introduced a simple analysis of the field strength that causes the prevailing unidirectional fiber deposition between neighbouring lamellae of a special saw-like collector. Few groups have also worked on producing aligned fibers by using collector plates of special designs [23][24][25]. But, it is difficult to understand how the electric field behaves in each of these types of collector designs.…”
Section: G R Rakesh G S Ranjit K K Karthikeyan P Radhakrishmentioning
confidence: 99%
“…Another approach was developed by Chvojka et al [22] who produced PVA nano yarns using a special saw-like collector, by twisting electrospun PVA nanofibers and introduced a simple analysis of the field strength that causes the prevailing unidirectional fiber deposition between neighbouring lamellae of a special saw-like collector. Few groups have also worked on producing aligned fibers by using collector plates of special designs [23][24][25]. But, it is difficult to understand how the electric field behaves in each of these types of collector designs.…”
Section: G R Rakesh G S Ranjit K K Karthikeyan P Radhakrishmentioning
confidence: 99%
“…[68] As a demonstration, we have recently shown that dural fibroblasts could cover the entire scaffold with a radial alignment at a faster speed relative to a scaffold made of random nanofibers. [69] A number of methods have been developed for controlling the alignment of electrospun nanofibers. These methods can be categorized into three major categories depending on the type of forces involved ( Fig.…”
Section: Controlling the Alignment Of Nanofibersmentioning
confidence: 99%
“…Since cells tend to migrate along the fibers, cells seeded around the periphery of a radially aligned scaffold would follow the nanofibers and migrate inward to cover the whole scaffold at a speed faster than if they were seeded on a scaffold made of random nanofibers. [69] Another useful type of alignment can be found in scaffolds that contain arrays of microwells. These scaffolds can be fabricated using an array of metallic beads as the collector (Fig.…”
Section: Alignment Caused By Electrostatic Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…2c). 222 In the subsequent studies, they generated microisland arrays of nanofibers with uniaxially aligned nanofibers in between (Fig. 2d) 223 and demonstrated that the nanoscale topographical guidance promoted skin cell migration in vitro and reepithelialization in vivo.…”
Section: Microfabrication Technologies To Provide Biochemical and Biomentioning
confidence: 97%